Thermogravimetric characteristics and kinetics of pyrolysis of coal blends - Juan Manuel Barraza-Burgos (Revista Facultad de Ingeniería Universidad de Antioquia, 2015)
Thermogravimetric characteristics and pyrolysis kinetics of coal blends were investigated using a thermogravimetric analyser under heating rate of 20°C/min, from room temperature to 850°C. Original coal samples were obtained from three Colombian regions: Valle del Cauca, South West (VAL), Antioquia, West Midlands (ANT) and Cundinamarca, Midlands (CUN). Coal blend samples (50-50 % w/w) were obtained from original coal of these three regions. The weight loss curves of coals obtained by thermogravimetry (TG) showed different trends. These may indicate that pyrolysis behaviours were not similar due to coal molecular structures have different chemical bonds. In addition, a kinetic analysis was performed to fi t TG data. In the analysis, it was assumed that a single chemical reaction described the pyrolysis of coals and coal blends. A Synergy Activation Energy Ratio (SAER) was defi ned in order to determine an additive effect between coals and coal blends, during pyrolysis. Obtained results showed that the SAER of the CUN-VAL coal blend is close to the unit, meaning that the blend has an additive behaviour. However, the SAER of ANT-VAL coal blend is lower than one, whereas of the ANT-CUN coal blend is higher than one. It suggests that VAL and CUN coals may have a non-additive reaction when they are blended with ANT coal.